Unveiling the unreal: Comprehensive imaging review of hepatic pseudolesions - Subramaniyan Ramanathan (14158842) (2021)
Hepatic pseudolesions are defined as non-neoplastic focal abnormalities of the liver which can mimic or conceal true liver lesions. It is particularly common in liver due to its unique dual blood supply and the existence of multilevel anastomosis between them. Because of the recent advances in CT and MRI technology, they are being increasingly encountered in daily practice. Broadly they can be categorised in to (1) Focal parenchymal abnormalities like focal fatty change, focal fat sparing, focal confluent fibrosis, segmental hypertrophy and regenerative nodules, (2) Perfusion abnormalities which include transient hepatic parenchymal enhancement in portal vein obstruction, third inflow, intrahepatic shunts, hepatic arterial occlusion and hepatic venous obstruction, (3) Imaging pitfalls like parenchymal compression, unenhanced vessels and pseudolipoma. It is essential for the radiologists to be familiar with the typical and atypical imaging features of pseudolesions to avoid mistaking them for sinister pathologies and also to avoid overlooking underlying hidden pathologies. Other Information Published in: Clinical Imaging License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.clinimag.2021.09.008